2019
DOI: 10.1186/s12885-019-5334-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage to sebaceous gland and the efficacy of moisturizer after whole breast radiotherapy: a randomized controlled trial

Abstract: BackgroundWe conducted a randomized trial to evaluate the efficacy of heparinoid moisturization for radiation dermatitis. We report the time-course of sebum content after whole breast radiotherapy (WBRT) and the efficacy of heparinoid moisturizer.MethodsPatients receiving adjuvant breast RT were randomly assigned into three groups; prophylaxis, post-WBRT and control groups. Patients used moisturizer on the irradiated breast from the beginning of RT in the prophylaxis group, 2 weeks post-RT in the post-WBRT gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…In contrast to this report, another study observed that sebum content is significantly reduced with radiotherapy. This study further reported that the application of a moisturizer could increase sebum levels in patients undergoing radiotherapy [ 26 ]. Both reports, like our study, used a photometric method for sebum measurement, evaluating the amount of sebum by analyzing the degree of light transmission in the measured area.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to this report, another study observed that sebum content is significantly reduced with radiotherapy. This study further reported that the application of a moisturizer could increase sebum levels in patients undergoing radiotherapy [ 26 ]. Both reports, like our study, used a photometric method for sebum measurement, evaluating the amount of sebum by analyzing the degree of light transmission in the measured area.…”
Section: Discussionmentioning
confidence: 84%
“…As radiotherapy damages the sebaceous gland and impairs the function of the stratum corneum [ 24 ], the amount of skin surface lipids may be altered by radiotherapy. Nonetheless, data regarding changes in sebum content during radiotherapy remain inconsistent [ 25 26 ]. In a study measuring the biophysical parameters before and after radiotherapy for breast cancer, sebum levels were not significantly altered following radiotherapy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32 Hirudoid Ⓡ is one of several available moisturizers that contain heparinoid, along with other ingredients such as white petrolatum, which are known to supplement stratum corneum water content and sebum. 4 , 6 Pain reduction following HP application has also been reported, although the relief was temporary. 4 , 5 Such effects of HP might contribute to shorten the period of “Symptoms and feelings” subscore worsening.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of radiation dermatitis begins with edematous erythema, then progresses to dry, desquamation plaque with pigmentation 104 . Several studies reported that irreversible disturbance of sebaceous glands occurs at the site of irradiation 104,105 . The major complications of radiation dermatitis are pruritus and skin tightness caused by asteatosis, requiring continuous treatment.…”
Section: Cq4 Are Moisturizers Useful For Treating Radiotherapy‐relate...mentioning
confidence: 99%